2008
DOI: 10.3390/entropy-e10020033
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Information Theory to the Quantification of Responses to Anthropogenic Noise by Southeast Alaskan Humpback Whales

Abstract: Abstract:We assess the effectiveness of applying information theory to the characterization and quantification of the affects of anthropogenic vessel noise on humpback whale (Megaptera novaeangliae) vocal behavior in and around Glacier Bay, Alaska. Vessel noise has the potential to interfere with the complex vocal behavior of these humpback whales which could have direct consequences on their feeding behavior and thus ultimately on their health and reproduction. Humpback whale feeding calls recorded during con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…There have been interesting debates on the nature of human emotions and the reliability of their acoustic detection, both in humans and in other primate and non-primate species [4,17,[44][45][46][47]. It is relevant that the three essential variables statistically discriminated in our previous study (energy, entropy, and F 0 ) appear repeatedly in the different experimental studies.…”
Section: Discussionmentioning
confidence: 93%
“…There have been interesting debates on the nature of human emotions and the reliability of their acoustic detection, both in humans and in other primate and non-primate species [4,17,[44][45][46][47]. It is relevant that the three essential variables statistically discriminated in our previous study (energy, entropy, and F 0 ) appear repeatedly in the different experimental studies.…”
Section: Discussionmentioning
confidence: 93%
“…Further studies along this line include the analysis of the chickadee (Parus atricapillus and P. carolinensis) [22,23], European starlings (Sturnus vulgaris) [24], Rufous-bellied thrushes (Turdus rufiventris) [25], European skylarks (Alauda arvensis L.) [26], wood thrushes (Hylocichla mustelina) and robins (Turdus migratorius) [13], bottlenose dolphins (Tursiops truncatus) [14,[27][28][29], humpback whales (Megaptera novaeangliae) [30][31][32][33] and male rock hyraxes (Procavia capensis) [34].…”
Section: Information Theory and Animal Communicationmentioning
confidence: 99%
“…These cries were investigated through the lens of information theory in several papers [30][31][32][33]. Suzuki [30] and Miksis-Olds and collaborators [31,32] analyzed the structure of humpback whale mating songs and found both that the sequences of whale cries were not stationary and could not be represented well by a first-order Markov chain model.…”
Section: Humpback Whalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Slabbekoorn and Peet [15] showed that some species of birds purposely sing at a higher pitch in a city environment than they do in quiet countryside, while Doyle et al [39] found that Humpback whales increase the rate and repetitiveness of their communication calls under the influence of marine vessel noise. This strategy is a variant of simply extending the duration of each component of the call and has the advantage that it avoids complete obscuration of a part of the call by a long burst of noise.…”
Section: Noisementioning
confidence: 99%